KAJIAN FASILITAS UMUM DESA MOROSARI DEMAK - Riskiyanto, Resza; Harani, Arnis Rochma; Atmoko, Rasyita; Hasan, Muhammad Ismail (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: Life's demands continue together with deteriorating natural conditions cause the community adjust its